IMPLIKASIHUMAN RESOURCE INFORMATION SYSTEM PADA PT. TELEKOMUNIKASI INDONESIA, TBK - Eka Kadharpa Utama Dewayani (Manajemen Bisnis, 2011)
Fakultas Ekonomi Universitas Muhammadiyah MalangE-mail: dewayani62@yahoo.co.idABSTRACTHuman Resource Information System has been giving a lot of advantages for employees and company. PT.Telekomunikasi Indonesia applies HRIS as a mean to conduct efficiency and to communication improvementamong its employee, so that HRD staff can be more focus at more strategic HRD activity. Thisresearch uses holistic single case study to answer four research questions. First question is about HRISusage in company. The implications of applying HRIS for HRM practice, the implication for employeeempowerment, the implication for knowledge sharing. Data collection is conducted over various datasources such as observation, interview, documentation, archival record, triangulation, and evaluation.The result of this research has indicated that HRIS application has supported company’s goal. Though itwas not represented yet the ideal applications and still in improvement process, but the existent is supportemployee’s work. The HRIS can be classified as integrated, interactive, context-sensitive self-direct byweb access types. Applying HRIS gives a positive influence on employee empowerment in the company.Some methods and processes in HRM practice are online. Applying give the easiness to do the knowledgesharing so that all employees are able to access all knowledge they required any time.Keywords: Human Resource Information System, Human Resource Management practice, employeeempowerment, knowledge sharing.